Filtering and sensing properties based on metal-dielectric-metal waveguide with slot cavities. Issue 14 (5th August 2016) - Li, Boxun; Li, Hongjian; Zeng, Lili; Zhan, Shiping; He, Zhihui; Chen, Zhiquan; Xu, Hui
Abstract: A triple-channel plasmonic system, consisting of several slot cavities coupled with the bus and drop waveguides, has been investigated numerically and theoretically. The impacts of adjusting various parameters on transmissivity are researched in detail. The results demonstrate that one can separate arbitrary wavelength and attain high transmissivity by suitably setting parameters. The sensitivity of the structure is about 950 nm shift per refractive index unit and the figure of merit is as high as 25.5. The plasmonic filter system possesses advantage of easy fabrication and compactness, which can find more applications in highly integrated optical devices, optical communication, and high sensitivity nano sensor.